2015
DOI: 10.1063/1.4907941
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical spectroscopic characterization at low temperatures of methyl hydroperoxide and three S-analogs

Abstract: The low temperature spectra of the detectable species methyl hydroperoxide (CH3OOH) and three sulfur analogs, the two isomers of methanesulfenic acid (CH3SOH and CH3OSH) and the methyl hydrogen disulfide (CH3SSH), are predicted from highly correlated ab initio methods (CCSD(T) and CCSD(T)-F12). Rotational parameters, anharmonic frequencies, torsional energy barriers, torsional energy levels, and their splittings are provided. Our computed parameters should help for the characterization and the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…0 0 + A 1 0.000 0.000 0.000 0.000 0.000 0.000 0 0 + A 1 0.000 0.000 0.000 0.000 0.000 0.000 0.000 Analysis of the data given in columns 2 and 4 of table 1 indicates excellent agreement in the values of the calculated energies of torsional states of the hydroxyl group obtained in this work and in [19], despite the different approaches to compiling the vibrational Schrӧdinger equation and a different number of points, in which the calculations of the potential energy were carried out. Comparable inferences can be made by analysing the data in columns 2 and 7 of table 2, where the calculations took into account the ZPVE in the harmonic approximation at the MP2/Aug-cc-pVTZ level of theory.…”
Section: Calculated At the Ccsd(t)/aug-cc-pvtz And Mp2/cbs Levels Of Theory And Using Two Methods For Determining The Value Of The Torsiosupporting
confidence: 73%
See 1 more Smart Citation
“…0 0 + A 1 0.000 0.000 0.000 0.000 0.000 0.000 0 0 + A 1 0.000 0.000 0.000 0.000 0.000 0.000 0.000 Analysis of the data given in columns 2 and 4 of table 1 indicates excellent agreement in the values of the calculated energies of torsional states of the hydroxyl group obtained in this work and in [19], despite the different approaches to compiling the vibrational Schrӧdinger equation and a different number of points, in which the calculations of the potential energy were carried out. Comparable inferences can be made by analysing the data in columns 2 and 7 of table 2, where the calculations took into account the ZPVE in the harmonic approximation at the MP2/Aug-cc-pVTZ level of theory.…”
Section: Calculated At the Ccsd(t)/aug-cc-pvtz And Mp2/cbs Levels Of Theory And Using Two Methods For Determining The Value Of The Torsiosupporting
confidence: 73%
“…It was found that the tunneling of the hydroxyl group in the ground state occurs at a frequency of 14.97 cm -1 , while the corresponding tunneling frequency of the methyl group was 7.64 ⋅ 10 -5 cm -1 . Recently [19], a more deep and detailed theoretical study of torsional vibrations in the MHP molecule was carried out. 2D potential energy surface (PES) for two torsional coordinates was calculated at a high level of theory (CCSD(T)/Aug-cc-pVTZ).…”
Section: Introductionmentioning
confidence: 99%
“…9 For the remaining structures, the angles between the heavy atoms are the following: C3N1C2 = 136. The CCSD(T)-F12/AVTZ-F12 equilibrium rotational constants of Table II were employed to determine the corresponding ground state parameters with the straightforward formula [26][27][28][29] B 0 = B e + ∆B core e + ∆B vib ,…”
Section: Equilibrium Geometries and Rotational Constantsmentioning
confidence: 99%
“…4 A better agreement is obtained with the parameters fitted by Koput 18 and Halfen et al, 3 although the differences |A 0 ab initio − A 0 exp | = 2315 MHz 18 and |A 0 ab initio − A 0 exp | = 2231 MHz 3 are too large if we compare them with the usual accuracy found when CCSD(T)-F12 theory is applied. [26][27][28][29] This method usually provides a precision of few MHz.…”
Section: Equilibrium Geometries and Rotational Constantsmentioning
confidence: 99%
See 1 more Smart Citation